Financing Early Psychosis Interventions: Provider Organization Perspectives. (20th August 2020) - Bao, Y.; Papp, M.; Lee, R.; Dixon, L.
Abstract : Research Objective: Coordinated Specialty Care (CSC) is an evidence‐based intervention for individuals experiencing first‐episode psychosis. A team of clinicians and nonclinical specialists deliver CSC based on the principles of shared decision making and aimed at maximizing recovery. Mental Health Block Grant (MHBG) "set‐aside" funding earmarked by Congress in 2014 (and doubled in 2015) boosted implementation of CSC in the U.S. Currently, CSC teams around the country utilize idiosyncratic and patchwork approaches to funding. This study aims to identify prominent models of CSC financing, alignments or misalignments of such models with sustained implementation, and CSC provider perspectives on ideal payment approaches. Study Design: Qualitative study based on semi‐structured interviews with informants from CSC provider organizations. A multi‐disciplinary team transcribed and analyzed digitally recorded interviews using the modified grounded theory method, iteratively developed a coding book, coded interview data, and identified recurring themes. Population Studied: Purposeful sampling of CSC program directors or team leaders using a national, far‐reaching email listserv was supplemented by snowball sampling via recommendation of interview participants. Findings are based on analysis of interview data of 15 CSC programs in 12 states. Principal Findings: A dominant model for CSC financing combined insurance billing (for billable services) and the MHBG funding (for nonbillable costs). CSC provider organizations viewed fee‐for‐service insurance billing as inadequate and seriously misaligned with CSC in the following ways: 1. Commercial insurance and Medicaid (to a less extent) typically do not cover services provided by nonclinician professionals (eg, supported employment and education specialists), services provided in the community, case management, or team operation and community outreach activities; 2. For covered services, the regular insurance billing rate is inadequate for the high intensity, low caseload of CSC; 3. Services provided prior to client enrollment (eg, to engage client and family) are often not covered; and 4. Insurance billing consumes substantial staff time and resources. CSC teams, regardless of their current financing approaches, almost universally endorsed a bundled/case rate payment as an ideal way of paying for CSC, with two major supporting rationales: 1. A bundled payment arrangement shifts the focus from "productivity" (in terms of billable encounters) to holistic problem‐solving and innovation with the explicit goal of improving patient engagement, outcomes, and experience; and 2. With a bundled payment, insured clients will not pick and choose which components of CSC to receive (eg, based on insurance coverage or out‐of‐pocket costs), thus preserving fidelity and provider autonomy in CSC service provision. Conclusions: Heavy reliance on fee‐for‐service insurance billing is unsustainable and misaligned with the goals of CSC. CSC provider organizations expressed high consensus in support of a bundled payment. Implications for Policy or Practice: To scale up and sustain population deployment of CSC, public and private payers should consider bundled payment approaches. Because of the diversity in CSC programs, populations, and existing funding mechanisms and rules, payer‐provider collaboration will be essential in designing the payment model. Data are needed to support the business case of covering CSC with a bundled rate, especially in terms of cost savings as a result of CSC. Primary Funding Source: The Robert Wood Johnson Foundation.